1998
DOI: 10.1242/dev.125.11.2087
|View full text |Cite
|
Sign up to set email alerts
|

sma-1 encodes a βH-spectrin homolog required for Caenorhabditis elegans morphogenesis

Abstract: Morphogenesis transforms the C. elegans embryo from a ball of cells into a vermiform larva. During this transformation, the embryo increases fourfold in length; present data indicates this elongation results from contraction of the epidermal actin cytoskeleton. In sma-1 mutants, the extent of embryonic elongation is decreased and the resulting sma-1 larvae, although viable, are shorter than normal. We find that sma-1 mutants elongate for the same length of time as wild-type embryos, but at a decreased rate. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…Therefore, we considered a more refined Economical Spatio-Temporal Growth model (ESTG), where d i,j is estimated by the Euclidean distance between neurons i and j at the time of birth of the newborn neuron, thereby adjusting for the fact that the connection distance between any pair of neurons will be shorter at earlier stages of development before the worm becomes elongated. We extrapolated the position of each neuron during growth from its position in the adult worm, assuming that each neuron's position was shifted along the this time, its body-length increases from 50µm to 1130µm [22][23][24]. b) In the adult hermaphrodite worm, more than 60% of the neurons are located in the head and about 15% are found in the tip of the tail (based on data modified according to [17], axis arbitrarily centred such that the origin is at the base of the head).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we considered a more refined Economical Spatio-Temporal Growth model (ESTG), where d i,j is estimated by the Euclidean distance between neurons i and j at the time of birth of the newborn neuron, thereby adjusting for the fact that the connection distance between any pair of neurons will be shorter at earlier stages of development before the worm becomes elongated. We extrapolated the position of each neuron during growth from its position in the adult worm, assuming that each neuron's position was shifted along the this time, its body-length increases from 50µm to 1130µm [22][23][24]. b) In the adult hermaphrodite worm, more than 60% of the neurons are located in the head and about 15% are found in the tip of the tail (based on data modified according to [17], axis arbitrarily centred such that the origin is at the base of the head).…”
Section: Resultsmentioning
confidence: 99%
“…longitudinal axis in proportion to the overall changes in body length (see Figure 1a) which we collated from the literature [22] (for the pre-hatching stage) and [23] (after hatching), using a linear interpolation between larval stages [24]. While the penalty on connection distance remains fixed in this model, its effect on connectivity as a function of the overall scaling of the system is dynamically evolving.…”
Section: Resultsmentioning
confidence: 99%
“…SMA-1) contribute to the correct architecture of AS-I ( McKeown et al, 1998 ). In AS-II, a DLG-1/Discs Large and AJM-1 complex (DAC) provides a link between the proposed adhesion molecule of the AS-II, called SAX-7/L1CAM ( Chen and Zhou, 2010 ), and cytoskeletal-associated components SMA-1/βH-spectrin, ERM-1/ezrin/radixin/moesin, and actin filaments ( Bernadskaya et al, 2011 ; Gobel et al, 2004 ; McKeown et al, 1998 ; Van Furden et al, 2004 ). A series of evolutionarily conserved ancillary proteins (actin filaments, claudins, spectrins and PAR proteins, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…3 b). sma-1 and sma-5 encode β H -spectrin and MAP kinase, respectively 22 , 23 . sma-8(e2111) is a dominant mutation for which the causative gene has not yet been identified.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that SMA-1 and SMA-5 appear to act in pathways parallel to that of DRAG-1. sma-1 encodes β H -spectrin, which is a very large spectrin found in invertebrates such as C. elegans and Drosophila 22 . The submembrane skeletal network is primarily formed from α2β2 spectrin tetramers, each composed of two α-spectrin and two β-spectrin subunits 31 .…”
Section: Discussionmentioning
confidence: 99%